Private capital flows to low‐income countries : the role of domestic financial sector. - Choong, Chee-Keong; Lam, Siew-Yong; Yusop, Zulkornain (Taylor & Francis, 2010)

(untitled)
The relationship between private capital flows and growth has been examined extensively in the literature, yet numerous controversies still remain. The study examines the relationships among private capital flows (foreign direct investment, portfolio investment and foreign debt), financial development and economic performance in a sample of 16 low-income developing countries over the period 1988–2006, by employing generalized method of moments (GMM) panel data analysis. We find that private capital flows have a positive impact on growth in low-income countries with well-developed financial sector but have a negative effect in the presence of poor financial sector development. Well-developed financial sectors are ones that are themselves crucial for economic growth. Our results indicate that private capital flows would be more effective if they were more systematically conditional on well-developed financial systems.